Method for degrading bpa-pc and its application in manufacturing epoxy thermosetting resin

CN119081229BActive Publication Date: 2026-10-20QINGDAO INST OF BIOENERGY & BIOPROCESS TECH CHINESE ACADEMY OF SCI
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411208148.4
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-08-30
Publication Date
2026-10-20
Estimated Expiration
2044-08-30

AI Technical Summary

Technical Problem

[0004]本发明针对现有BPA-PC塑料高效升级再利用的问题,提供一种用BPA-PC的降解产物制备环氧热固性树脂的方法,将BPA-PC的降解与环氧热固性树脂的合成相耦合,实现BPA-PC塑料高效升级再利用

Benefits of technology

[0022]本发明将BPA-PC的降解与环氧热固性树脂的合成相耦合,实现BPA-PC高效转化为环氧热固性材料,为废旧塑料的化学回收开辟一条新途径。同时这一过程无需对BPA-PC的降解产物进行分离和纯化,也不涉及过量的反应试剂,解聚产物可以直接实现高效的再利用,实现了100%的原子利用率。此外,本发明制备的环氧热固性树脂具有良好的力学性能、热学性能、动态性能等综合性能,同时其结构中保留碳酸酯键,可实现化学循环。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119081229B_ABST
    Figure CN119081229B_ABST
Patent Text Reader

Abstract

The application discloses a BPA-PC degradation method and application thereof in manufacturing of epoxy thermosetting resin, and belongs to the technical field of depolymerization recycling of high polymer composite materials. The application couples the degradation of BPA-PC with the synthesis of epoxy thermosetting resin, realizes efficient upgrading and recycling of BPA-PC plastic, and opens up a new way for chemical recycling of waste plastic. The application uses diphenyl carbonate as a depolymerization reagent to realize the depolymerization of BPA-PC, and the obtained depolymerization product is directly used as a curing agent of epoxy resin without separation and purification, so that high-performance and recyclable epoxy thermosetting resin is prepared. The process does not involve excessive reaction reagents, the depolymerization product can be directly recycled, and 100% atom utilization rate is realized. In addition, the prepared epoxy thermosetting resin has good comprehensive performances such as mechanical properties, thermal properties and dynamic properties, and meanwhile, carbonate bonds are reserved in the structure of the epoxy thermosetting resin, so that chemical recycling can be realized.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to a BPA-PC degradation method and its application in the manufacture of epoxy thermosetting resins, belonging to the field of polymer composite material depolymerization, recycling and reuse technology. Background Technology

[0002] Bisphenol A (BPA) polycarbonate (BPA-PC) is an important engineering plastic widely used in packaging, automotive parts, and other fields, with huge global consumption. However, because waste BPA-PC slowly releases ecotoxically toxic bisphenol A into the environment, its recycling is crucial.

[0003] Chemical recycling is an effective means of recycling BPA-PC. However, previous reports on BPA-PC chemical recycling often involve nucleophiles attacking carbonate bonds, using them as a green source of carbonyl groups to synthesize carbonyl-containing chemicals, accompanied by the formation of the monomer bisphenol A. For example, patent CN 113912559 B reports the use of the highly nucleophilic reagent ethanolamine for ammonialysis to obtain the product oxazolidinone. Although these carbonyl-containing depolymerization products are touted as having high added value, their actual application market needs further consideration, and the economic viability of the recycling process compared to conventional production methods for these chemicals has not been verified. Therefore, it is essential to provide a method that eliminates the need for complex separation processes and excessive reaction reagents, allowing for the efficient reuse of depolymerization products, thereby achieving the efficient upgrading and reuse of BPA-PC plastics. Summary of the Invention

[0004] This invention addresses the problem of efficient upgrading and reuse of existing BPA-PC plastics by providing a method for preparing epoxy thermosetting resins using BPA-PC degradation products. This method couples the degradation of BPA-PC with the synthesis of epoxy thermosetting resins, thereby achieving efficient upgrading and reuse of BPA-PC plastics.

[0005] The technical solution of the present invention:

[0006] One objective of this invention is to provide a method for degrading BPA-PC, which involves mixing BPA-PC with diphenyl carbonate, adding a depolymerization catalyst, heating the mixture to obtain a depolymerization product, which can be used as an epoxy resin curing agent.

[0007] Further specifying, the number-average molecular weight of BPA-PC is 10. 2 ~10 7 g / mol.

[0008] Further specified, the amount of diphenyl carbonate accounts for 10 to 100% of the amount of BPA-PC.

[0009] Further specifying, the depolymerization catalyst is one or more combinations of sodium hydroxide, potassium hydroxide, sodium phenolate, and potassium phenolate.

[0010] Further specifying, the amount of the depolymerization catalyst is 0.01 to 1% of the molar amount of the BPA-PC repeating unit.

[0011] Further specified, the heating reaction temperature is 100–250℃, and the time is 1–24h.

[0012] The second objective of this invention is to provide an application of the above-mentioned BPA-PC degradation method in the manufacture of epoxy thermosetting resins, the application method comprising the following steps:

[0013] (1) Mix BPA-PC with diphenyl carbonate, add a depolymerization catalyst, heat the reaction to obtain the depolymerization product;

[0014] (2) Mix the depolymerization product, epoxy resin and curing catalyst, and heat to cure to obtain epoxy thermosetting resin.

[0015] Further specified, (2) the curing catalyst is 4-dimethylaminopyridine DMAP or pyridine, and the mass of the curing catalyst added is 0.01 to 1% of the mass of the epoxy resin.

[0016] Further specifying, (2) the molar ratio of the epoxy group of the epoxy resin to the carbonate group of the depolymerization product is 1:1.

[0017] Further specifying, in (2), epoxy resin is a compound whose molecular structure contains two or more epoxy groups.

[0018] To further specify, the epoxy resin is bisphenol A diglycidyl ether, with the structure shown below:

[0019]

[0020] Further specified, (2) the curing temperature is 80~250℃ and the time is 1~24h.

[0021] Beneficial effects:

[0022] This invention couples the degradation of BPA-PC with the synthesis of epoxy thermosetting resin, achieving the efficient conversion of BPA-PC into epoxy thermosetting materials and opening a new pathway for the chemical recycling of waste plastics. Simultaneously, this process eliminates the need for separation and purification of BPA-PC degradation products and avoids the use of excessive reaction reagents; the depolymerization products can be directly and efficiently reused, achieving 100% atom utilization. Furthermore, the epoxy thermosetting resin prepared by this invention possesses excellent comprehensive properties, including mechanical, thermal, and dynamic properties, while retaining carbonate bonds in its structure, enabling chemical recycling. Attached Figure Description

[0023] Figure 1 The graph shows the dynamic thermomechanical analysis test results of the thermosetting epoxy resin obtained in Example 1.

[0024] Figure 2 The stress-strain curve of the thermosetting epoxy resin obtained in Example 1 is shown in the figure.

[0025] Figure 3 The graph shows the thermogravimetric analysis results of the thermosetting epoxy resin obtained in Example 1. Detailed Implementation

[0026] To make the above-mentioned objects, features and advantages of the present invention more apparent and understandable, the specific embodiments of the present invention will be described in detail below with reference to the examples in the specification.

[0027] Many specific details are set forth in the following description in order to provide a full understanding of the invention. However, the invention may also be practiced in other ways different from those described herein, and those skilled in the art can make similar extensions without departing from the spirit of the invention. Therefore, the invention is not limited to the specific embodiments disclosed below.

[0028] Secondly, the term "one embodiment" or "embodiment" as used herein refers to a specific feature, structure, or characteristic that may be included in at least one implementation of the present invention. The phrase "in one embodiment" appearing in different places in this specification does not necessarily refer to the same embodiment, nor is it a single or selective embodiment that is mutually exclusive with other embodiments.

[0029] Unless otherwise specified, the experimental methods used in the following examples are conventional methods. Unless otherwise specified, all materials, reagents, methods, and instruments used are conventional materials, reagents, methods, and instruments in the art, and can be obtained commercially by those skilled in the art. Furthermore, all solid and liquid reagents used are of analytical grade.

[0030] Example 1

[0031] The reaction process for preparing epoxy thermosetting resin using the degradation products of BPA-PC in this embodiment is as follows:

[0032]

[0033] The specific operating procedure is as follows:

[0034] PhONa (2.28 mg, 0.02 mmol, 0.05% equiv.) was weighed and added to a 50 mL round-bottom flask; BPA-PC granules (molecular weight 21000 g / mol, molecular weight distribution 2.3) (10 g, 0.039 mol, 1 equiv.) and DPC (8.43 g, 0.039 mol, 1 equiv.) were weighed and added to the flask, and the mixture was stirred at 200 °C for 4 h to obtain the depolymerization product DPC-PC.

[0035] DPC-PC (6g, 12.8mmol, 1equiv.) and DGEBA (4.36g, 12.8mmol, 1equiv.) were weighed and added to a round-bottom flask. 31g of anhydrous THF was added and dissolved to prepare a 25% wt solution. DMAP (10.9mg, 0.25% wt epoxy) was weighed and added to the flask. After the DMAP was completely dissolved and the system became a homogeneous solution, the solution was poured into a PTFE mold. After the THF solvent evaporated and dried, the sample was placed in a vacuum drying oven at 60℃ for 12h to remove bubbles. After degassing, the sample was cured by staged temperature increases to obtain a thermosetting epoxy resin. Curing conditions: argon atmosphere, 80℃ (4h) → 120℃ (2h) → 140℃ (2h) → 160℃ (2h) → 180℃ (2h) → 200℃ (2h) → 220℃ (2h).

[0036] The obtained thermosetting epoxy resin was subjected to property testing using a dynamic thermomechanical analyzer. The results are as follows: Figure 1 As shown, its glass transition temperature is 146℃, its storage modulus at room temperature is 2.9 GPa, and its crosslinking density is 2170 mol / m³. 3 The stress-strain curves were analyzed through tensile tests, and the test results are as follows: Figure 2 As shown, its fracture strength was measured to be 71 MPa, and its elongation at break was 9.5%. Thermogravimetric analysis yielded the following results: Figure 3 As shown, the temperature at which 5% mass loss is measured is 352℃.

[0037] Example 2

[0038] The difference between this embodiment and Embodiment 1 is that BPA-PC water tanks (molecular weight 25500g / mol, molecular weight distribution 2.5) are used instead of BPA-PC granules.

[0039] The specific operating procedure is as follows:

[0040] PhONa (2.28 mg, 0.02 mmol, 0.05% equiv.) was weighed and added to a 50 mL round-bottom flask; BPA-PC (molecular weight 25500 g / mol, molecular weight distribution 2.5) (10 g, 0.039 mol, 1 equiv.) and DPC (8.43 g, 0.039 mol, 1 equiv.) were weighed and added to the flask, and the mixture was stirred at 200 °C for 8 h to obtain the depolymerization product DPC-PC.

[0041] DPC-PC (6g, 12.8mmol, 1equiv.) and DGEBA (4.36g, 12.8mmol, 1equiv.) were weighed and added to a round-bottom flask. 31g of anhydrous THF was added and dissolved to prepare a 25% wt solution. DMAP (10.9mg, 0.25% wt epoxy) was weighed and added to the flask. After the DMAP was completely dissolved and the system became a homogeneous solution, the solution was poured into a PTFE mold. After the THF solvent evaporated and dried, the sample was placed in a vacuum drying oven at 60℃ for 12h to remove bubbles. After degassing, the sample was cured by staged temperature increases to obtain a thermosetting epoxy resin. Curing conditions: argon atmosphere, 80℃ (4h) → 120℃ (2h) → 140℃ (2h) → 160℃ (2h) → 180℃ (2h) → 200℃ (2h) → 220℃ (2h).

[0042] The obtained thermosetting epoxy resin was subjected to property tests. Using a dynamic thermomechanical analyzer, its glass transition temperature was 145℃, its storage modulus at room temperature was 2.8 GPa, and its crosslinking density was 2180 mol / m³. 3 The stress-strain curve was analyzed by tensile test, and its breaking strength was measured to be 70 MPa and its breaking elongation was 9.8%. The 5% mass loss temperature was measured to be 355℃ by thermogravimetric analysis.

[0043] Example 3

[0044] The difference between this embodiment and Embodiment 1 is that BPA-PC optical discs (molecular weight 14500 g / mol, molecular weight distribution 2.3) are used instead of BPA-PC granules.

[0045] The specific operating procedure is as follows:

[0046] PhONa (2.28 mg, 0.02 mmol, 0.05% equiv.) was weighed and added to a 50 mL round-bottom flask; BPA-PC optical disc (molecular weight 14500 g / mol, molecular weight distribution 2.3) (10 g, 0.039 mol, 1 equiv.) and DPC (8.43 g, 0.039 mol, 1 equiv.) were weighed and added to the flask, and the mixture was stirred at 200 °C for 8 h to obtain the depolymerization product DPC-PC.

[0047] DPC-PC (6g, 12.8mmol, 1equiv.) and DGEBA (4.36g, 12.8mmol, 1equiv.) were weighed and added to a round-bottom flask. 31g of anhydrous THF was added and dissolved to prepare a 25% wt solution. DMAP (10.9mg, 0.25% wt epoxy) was weighed and added to the flask. After the DMAP was completely dissolved and the system became a homogeneous solution, the solution was poured into a PTFE mold. After the THF solvent evaporated and dried, the sample was placed in a vacuum drying oven at 60℃ for 12h to remove bubbles. After degassing, the sample was cured by staged temperature increases to obtain a thermosetting epoxy resin. Curing conditions: argon atmosphere, 80℃ (4h) → 120℃ (2h) → 140℃ (2h) → 160℃ (2h) → 180℃ (2h) → 200℃ (2h) → 220℃ (2h).

[0048] The obtained thermosetting epoxy resin was subjected to property testing. Using a dynamic thermomechanical analyzer, its glass transition temperature was 141℃, its storage modulus at room temperature was 2.7 GPa, and its crosslinking density was 1970 mol / m³. 3 The stress-strain curve was analyzed by tensile testing, and its breaking strength was found to be 68 MPa, and its breaking elongation was 8.3%. The 5% mass loss temperature was found to be 348℃ by thermogravimetric analysis.

[0049] Example 4

[0050] The difference between this embodiment and Example 1 is that the amount of DPC used is 0.020 mol (4.22 g, 0.5 equiv.).

[0051] The specific operating procedure is as follows:

[0052] PhONa (2.28 mg, 0.02 mmol, 0.05% equiv.) was weighed and added to a 50 mL round-bottom flask; BPA-PC granules (molecular weight 21000 g / mol, molecular weight distribution 2.3) (10 g, 0.039 mol, 1 equiv.) and DPC (4.22 g, 0.020 mol, 0.5 equiv.) were weighed and added to the flask, and the mixture was stirred at 200 °C for 8 h to obtain the depolymerization product DPC-PC-2.

[0053] Weigh DPC-PC-2 (6.16 g, 12.8 mmol, 1 equivalent) and DGEBA (4.36 g, 12.8 mmol, 1 equivalent) into a round-bottom flask, add 31 g of anhydrous THF and dissolve evenly to prepare a 25% wt solution. Weigh DMAP (10.9 mg, 0.25% wt epoxy) and add it to the flask. After the DMAP is completely dissolved and the system is a homogeneous solution, pour the solution into a PTFE mold. After the THF solvent evaporates and the sample is dried, place it in a vacuum drying oven at 60°C for 12 h to remove bubbles. After degassing, the sample is cured by staged temperature increases to obtain thermosetting epoxy resin. Curing conditions: under argon atmosphere, 80°C (4 h) → 120°C (2 h) → 140°C (2 h) → 160°C (2 h) → 180°C (2 h) → 200°C (2 h) → 220°C (2 h).

[0054] The obtained thermosetting epoxy resin was subjected to property tests. Using a dynamic thermomechanical analyzer, its glass transition temperature was 149℃, its storage modulus at room temperature was 2.8 GPa, and its crosslinking density was 2210 mol / m³. 3 The stress-strain curve was analyzed by tensile testing, and its breaking strength was found to be 69 MPa, and its breaking elongation was 8.9%. The 5% mass loss temperature was found to be 357℃ by thermogravimetric analysis.

[0055] Example 5

[0056] The difference between this embodiment and Embodiment 1 is that the depolymerization temperature is 180℃ and the time is 8h.

[0057] The specific operating procedure is as follows:

[0058] PhONa (2.28 mg, 0.02 mmol, 0.05% equiv.) was weighed and added to a 50 mL round-bottom flask; BPA-PC granules (molecular weight 21000 g / mol, molecular weight distribution 2.3) (10 g, 0.039 mol, 1 equiv.) and DPC (8.43 g, 0.039 mol, 1 equiv.) were weighed and added to the flask, and the mixture was stirred at 180 °C for 8 h to obtain the depolymerization product DPC-PC.

[0059] DPC-PC (6g, 12.8mmol, 1equiv.) and DGEBA (4.36g, 12.8mmol, 1equiv.) were weighed and added to a round-bottom flask. 31g of anhydrous THF was added and dissolved to prepare a 25% wt solution. DMAP (10.9mg, 0.25% wt epoxy) was weighed and added to the flask. After the DMAP was completely dissolved and the system became a homogeneous solution, the solution was poured into a PTFE mold. After the THF solvent evaporated and dried, the sample was placed in a vacuum drying oven at 60℃ for 12h to remove bubbles. After degassing, the sample was cured by staged temperature increases to obtain a thermosetting epoxy resin. Curing conditions: argon atmosphere, 80℃ (4h) → 120℃ (2h) → 140℃ (2h) → 160℃ (2h) → 180℃ (2h) → 200℃ (2h) → 220℃ (2h).

[0060] The obtained thermosetting epoxy resin was subjected to property tests. Using a dynamic thermomechanical analyzer, its glass transition temperature was 143℃, its storage modulus at room temperature was 2.7 GPa, and its crosslinking density was 2310 mol / m³. 3 The stress-strain curve was analyzed by tensile testing, and its breaking strength was found to be 68 MPa and its breaking elongation was 8.1%. The 5% mass loss temperature was found to be 346℃ by thermogravimetric analysis.

[0061] Example 6

[0062] The difference between this embodiment and Embodiment 1 is that the depolymerization temperature is 160℃ and the time is 15h.

[0063] The specific operating procedure is as follows:

[0064] PhONa (2.28 mg, 0.02 mmol, 0.05% equiv.) was weighed and added to a 50 mL round-bottom flask; BPA-PC granules (molecular weight 21000 g / mol, molecular weight distribution 2.3) (10 g, 0.039 mol, 1 equiv.) and DPC (8.43 g, 0.039 mol, 1 equiv.) were weighed and added to the flask, and the mixture was stirred at 160 °C for 15 h to obtain the depolymerization product DPC-PC.

[0065] DPC-PC (6g, 12.8mmol, 1equiv.) and DGEBA (4.36g, 12.8mmol, 1equiv.) were weighed and added to a round-bottom flask. 31g of anhydrous THF was added and dissolved to prepare a 25% wt solution. DMAP (10.9mg, 0.25% wt epoxy) was weighed and added to the flask. After the DMAP was completely dissolved and the system became a homogeneous solution, the solution was poured into a PTFE mold. After the THF solvent evaporated and dried, the sample was placed in a vacuum drying oven at 60℃ for 12h to remove bubbles. After degassing, the sample was cured by staged temperature increases to obtain a thermosetting epoxy resin. Curing conditions: argon atmosphere, 80℃ (4h) → 120℃ (2h) → 140℃ (2h) → 160℃ (2h) → 180℃ (2h) → 200℃ (2h) → 220℃ (2h).

[0066] The obtained thermosetting epoxy resin was subjected to property testing. Using a dynamic thermomechanical analyzer, its glass transition temperature was 149℃, its storage modulus at room temperature was 2.9 GPa, and its crosslinking density was 2290 mol / m³. 3 The stress-strain curve was analyzed by tensile testing, and its breaking strength was found to be 70 MPa and its elongation at break was 8.3%. The 5% mass loss temperature was found to be 353℃ by thermogravimetric analysis.

[0067] Example 7

[0068] The difference between this embodiment and embodiment 1 is that the curing conditions in this embodiment are: 80℃ (4h) → 120℃ (2h) → 140℃ (2h) → 160℃ (2h) → 180℃ (2h) under an argon atmosphere.

[0069] The specific operating procedure is as follows:

[0070] PhONa (2.28 mg, 0.02 mmol, 0.05% equiv.) was weighed and added to a 50 mL round-bottom flask; BPA-PC granules (molecular weight 21000 g / mol, molecular weight distribution 2.3) (10 g, 0.039 mol, 1 equiv.) and DPC (8.43 g, 0.039 mol, 1 equiv.) were weighed and added to the flask, and the mixture was stirred at 180 °C for 8 h to obtain the depolymerization product DPC-PC.

[0071] DPC-PC (6g, 12.8mmol, 1equiv.) and DGEBA (4.36g, 12.8mmol, 1equiv.) were weighed and added to a round-bottom flask. 31g of anhydrous THF was added and dissolved to prepare a 25% wt solution. DMAP (10.9mg, 0.25% wt epoxy) was weighed and added to the flask. After the DMAP was completely dissolved and the system became a homogeneous solution, the solution was poured into a PTFE mold. After the THF solvent evaporated and dried, the sample was placed in a vacuum drying oven at 60℃ for 12h to remove bubbles. After degassing, the sample was cured by staged temperature increases to obtain a thermosetting epoxy resin. Curing conditions: 80℃ (4h) → 120℃ (2h) → 140℃ (2h) → 160℃ (2h) → 180℃ (2h) under an argon atmosphere.

[0072] The obtained thermosetting epoxy resin was subjected to property tests. Using a dynamic thermomechanical analyzer, its glass transition temperature was 136℃, its storage modulus at room temperature was 2.5 GPa, and its crosslinking density was 1850 mol / m³. 3 The stress-strain curve was analyzed by tensile testing, and its breaking strength was found to be 64 MPa, with an elongation at break of 5.7%. The 5% mass loss temperature was found to be 333℃ by thermogravimetric analysis.

[0073] Although the present invention has been disclosed above with reference to preferred embodiments, it is not intended to limit the present invention. Anyone skilled in the art can make various modifications and alterations without departing from the spirit and scope of the present invention. Therefore, the scope of protection of the present invention should be determined by the claims.

Claims

1. A method for preparing an epoxy thermosetting resin, characterized in that, include: (1) Mix BPA-PC with diphenyl carbonate, add a depolymerization catalyst, heat the mixture to react, and obtain the depolymerization product; (2) Mix the depolymerization product, epoxy resin and curing catalyst, and heat to cure to obtain epoxy thermosetting resin; The curing catalyst in (2) is 4-dimethylaminopyridine DMAP or pyridine. The mass of the curing catalyst added is 0.01~1% of the mass of the epoxy resin. The molar ratio of the epoxy group of the epoxy resin to the carbonate group in the depolymerization product is 1:

1.

2. The preparation method according to claim 1, characterized in that, (1) The number-average molecular weight of BPA-PC is 10. 2 ~10 7 g / mol.

3. The preparation method according to claim 1, characterized in that, (1) The amount of diphenyl carbonate accounts for 10 to 100% of the amount of BPA-PC.

4. The preparation method according to claim 1, characterized in that, (1) The depolymerization catalyst is one or more of sodium hydroxide, potassium hydroxide, sodium phenolate, and potassium phenolate.

5. The preparation method according to claim 1, characterized in that, (1) The amount of the depolymerization catalyst is 0.01~1% of the molar amount of the BPA-PC repeating unit.

6. The preparation method according to claim 1, characterized in that, (1) The heating reaction temperature is 100~250℃ and the time is 1~24 h.

7. The preparation method according to claim 1, characterized in that, (2) Epoxy resin is a compound whose molecular structure contains two or more epoxy groups.

Citation Information

Patent Citations

  • Epoxy resin composition

    CN112752781A

  • Method for degrading polycarbonate by using phenol catalyst

    CN117024846A